Comparative evaluation of flexural strength and depth of penetration following dentin pretreatment with proanthocyanidin and phytosphingosine. Issue 15 (3rd August 2021) - Shriram, Shanthi; Aruna Rani, S. V.; Kritika, Selvakumar; Balasubramanian, Saravana Karthikeyan; Rajkumar, Kothandaraman; Mahalaxmi, Sekar
Abstract: This study aimed to comparatively evaluate the cell viability, flexural strength (FS) and depth of penetration following surface pretreatment of demineralized dentin with phytosphingosine (PHS) and proanthocyanidin (PAC). Cytotoxicity of PAC and PHS was assessed by MTT assay on mouse fibroblasts. 52 dentin slabs from human mandibular molars were randomly divided into 4 groups for FS analysis ( n  = 13); groups I (negative control)- no intervention, II (positive control)- etching, bonding and composite buildup, III and IV- pretreatment with 6.5% PAC and 6.5% PHS respectively for 10 min followed by bonding protocol. For depth of penetration, groups I (no pre-treatment), II (PAC) and III (PHS) with bonding protocols similar to FS analysis were evaluated. Results were statistically analysed by Kolmogorov-Smirnov test, one-way ANOVA and post hoc tukey test ( p  < 0.05). MTT assay revealed 96.7% and 91.06% at 10 µg/mL of PAC and PHS respectively. There was a significant difference in FS between control groups [I (0.91 ± 0.54), II (0.60 ± 0.27)], while there was no difference between experimental groups [III (1.13 ± 0.10), IV (1.10 ± 0.08)]. Statistical significant differences were observed in depth of penetration among three groups [I (14.50 ± 2.95), II (33.67 ± 2.42) and III (47.67 ± 2.80)]. Therefore, PHS may serve as a promising alternative to PAC when applied over demineralized dentin.